Environment and admission preferences of 16–17 year olds - Samantha Jones; Damian Roland; Hannah Siu-Yu Ha (BMJ Paediatrics Open)
This is a short letter highlighting findings from a service evaluation of 16–17 year olds’ preferences of location of care following presentation to an Emergency Department. 95 young people were interviewed; 54.7% (52/95) of participants preferred to be seen in the Paediatric Emergency Department, with 16 year olds showing a higher preference (62.2%) compared with 17 year olds (48.0%). Additionally, 58.9% (56/95) desired a choice in treatment location, and 67.4% (64/95) expressed a preference for age-specific wards during admissions. Our findings highlight the importance of recognising the individual needs and preferences of young people within healthcare.